PENANGANAN KOMPLAIN DI RUMAH SAKIT - Irene Waine; Andreasta Meliala; Valentina Dwi Yuli Siswianti (Journal of Health Service Management, 2020)
Background: Complaint management is a strategy used by agencies in dealing with consumer complaints. Seeing consumer complaintsis an opportunity for agencies to retain consumers. Through an effective complaint handling process, information from customerswill be obtained as input in improving and developing agency service activities. Complaints are a form of dissatisfaction with informationor services received. Thus, complaints can solve customer dissatisfaction problems in hospital services to improve hospital quality.Objective: This study aims to evaluate the effectiveness of handling complaints at the Panti Rapih Hospital.Methods: This research is qualitative. Subjects in the study were ten officers who often handled complaints. The study was conductedin May-June 2019 at Panti Rapih Hospital.Results: The availability of supporting facilities is adequate, including complaint channels via SMS, email, via telephone, suggestionbox, complaint sheet. All staff have received training in effective communication. The flow and procedures for handling complaintshave been maximized. However, their many complaints are still repeated. The process of monitoring and evaluating complaint handlingreporting documentation has been running optimally. The response time for handling complaints is perfect because all casesare handled on average 1x24 hours, the response time reaches 95%.Conclusion: The handling of complaints at the Panti Rapih Hospital has been maximized but ineffective. The handling is not yet effectivebecause the information system process does not support the complaint handling process, for example, the delivery of information topatients who have not been able to in real-time. The mechanism for handling complaints is carried out by submitting complaints verballyand in writing to the maximum extent.